Removal and recovery of thallium from aqueous solutions via a magnetite-mediated reversible adsorption-desorption process. (20th October 2018) - Li, Huosheng; Li, Xiuwan; Chen, Yongheng; Long, Jianyou; Zhang, Gaosheng; Xiao, Tangfu; Zhang, Ping; Li, Changlin; Zhuang, Lingzhi; Huang, Wenyu
Abstract: Thallium (Tl), an extremely toxic heavy metal, has received much less attention than other toxic heavy metals such as Hg, Cd, and Pb. To date, Tl pollution control studies have usually focused on its removal only, while very few studies have explored its recovery from wastewater. In this study, a magnetite (Fe3 O4 )-mediated reversible adsorption-desorption process for the removal and recovery of Tl(I) from wastewater was investigated. Fast and efficient removal of Tl(I) was achieved via adsorption under alkaline conditions at pH > 11.0, while rapid and effective enrichment of Tl(I) was achieved via desorption under acidic conditions at pH < 3.0. The Tl adsorption was effective under high ionic strength even when multiple cations were present. Furthermore, efficient removal of Tl was also observed when magnetite was applied to the treatment of real industrial wastewater. Fourier transform infrared and X-ray photoelectron spectroscopic studies reveal that surface complexation and electrostatic attraction are the main mechanisms of Tl(I) removal. The removal and recovery of Tl(I) could be effectively and stably repeated without obvious loss of magnetite, indicating that the magnetite-based reversible adsorption-desorption process is a promising technique that can be developed further. Graphical abstract: Image 1 Highlights: Magnetite is efficient for Tl removal from both synthetic and real wastewaters. Tl removed at pH > 11.0 via adsorption and Tl recovered at pH < 3.0 via desorption. Selectivity and recyclability for Tl removal are excellent. Surface complexation and electroneutral attraction are the main mechanisms for Tl removal.